2024
DOI: 10.3389/fphar.2024.1353620
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dexmedetomidine on postoperative nausea and vomiting in female patients undergoing radical thoracoscopic lung cancer resection

Haipeng Zhu,
Shichao Wang,
Ruohan Wang
et al.

Abstract: Introduction: Postoperative nausea and vomiting (PONV) is a prevalent postsurgical complication. The objective of our study was to compare the effect of different doses of dexmedetomidine on PONV in female patients undergoing radical thoracoscopic lung cancer resection.Methods: A total of 164 female patients undergoing elective thoracoscopic radical lung cancer surgery were enrolled and assigned to one of four groups. Patients received 0.2 μg/kg/h, 0.4 μg/kg/h, 0.8 μg/kg/h dexmedetomidine and normal saline in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Dexmedetomidine is a highly selective α-2 adrenergic receptor agonist and possesses analgesic, anxiolytic, sympatholytic effects. Recent clinical trials revealed that dexmedetomidine can reduce the incidence of PONV after dental rehabilitation and thoracoscopic lung cancer resection [ 32 , 33 ]. Pregabalin is a structural gama-aminobutyric acid (GABA) analogue that is frequently preferred for neuropathic pain.…”
Section: Discussionmentioning
confidence: 99%
“…Dexmedetomidine is a highly selective α-2 adrenergic receptor agonist and possesses analgesic, anxiolytic, sympatholytic effects. Recent clinical trials revealed that dexmedetomidine can reduce the incidence of PONV after dental rehabilitation and thoracoscopic lung cancer resection [ 32 , 33 ]. Pregabalin is a structural gama-aminobutyric acid (GABA) analogue that is frequently preferred for neuropathic pain.…”
Section: Discussionmentioning
confidence: 99%